VALIDITY AND RELIABILITY OF THE SATISFACTION MEASUREMENT SCALE ON PEDESTRIAN PATHS IN KENDARI CITY - Henny Adi; M. Arzal Tahir; Nahdatunnisa Nahdatunnisa; Ade Wahyudi (Indonesian Journal of Multidisciplinary Science, 2022)
The purpose of this study was to test the validity and reliability of the importance and satisfaction scale of pedestrian paths in the green open space area of ??Kendari City and to find out which indicators have the greatest contribution to each research variable. The indicators used in this study include: accessibility, connectivity, circulation, security, safety, noise, beauty, climate and cleanliness to determine the priority of services needed to improve the performance of pedestrian path facilities. This study uses 27 research variables which are a combination of quantitative and qualitative research, with a sample of 399 respondents on the pedestrian path users of Green Open Space (RTH). Data retrieval was carried out using a scale of importance and a satisfaction scale that was compiled with a Likert Scale model. The data were analyzed using the SPSS Version 26 method. The validity test aims to assess the extent to which the measuring instrument is believed to be used as a tool to measure the research questions. Test the validity by comparing the values ??of rcount and rtable. If the value of rcount > rtable, then the item is declared valid, and vice versa. It is known that n = 30 5% significance then the value of rtable = 0.361.iate between departments in the same organization). The variables of accessibility, connectivity, circulation, security, comfort, safety, beauty, climate/shade and cleanliness show that the Pearson Correlation value for each question item for the 9 variable instrument is greater than rtable = 0.361. In addition, the overall significance value is smaller than 0.05. So that the question indicator of all 9 variable instruments has a valid construct. Reliability test was conducted to measure the level of consistency of a measuring instrument used at different times. The test was carried out using the Alpha method from Cronbach. The instrument is declared reliable if the calculation results show the Cronbach Alpha value > 0.6. The results showed that the Cronbach Alpha value of each instrument variable in the study had a value > 0.60, thus it can be stated that the instrument's accessibility, connectivity, circulation, security, safety, noise, beauty, climate/safety and cleanliness are reliable.